The effects of critical thinking instruction through asynchronous learning tools on writing - Sibel Aygün; Fatih Yavuz (Universitas Islam Sultan Agung, 2020)
In writing classes, besides mastering the language items and writing rhetoric, students are required to use some high order thinking skills to be able to write academically. Hence, this study basically aims to see the effectiveness of the use of critical thinking skills on writing achievements of the Turkish EFL students. The purpose of the study is to see if online critical thinking treatment affects students’ use of critical thinking skills in their writings. In addition, students’ attitudes towards asynchronous learning tools during the study were observed. At the beginning and end of the study, 16 students in control group and 16 students in experimental group answered the questions in the critical thinking disposition scale. In addition to this, their writing performances were evaluated before and after the study. Meanwhile, experimental group students were exposed to 8-week online critical thinking treatment. The data gathered were statistically analysed and the results indicate that while the students’ writing performances do not differ significantly before and after the online critical thinking treatment, it has significantly contributed to the studentS’ use of critical thinking skills while writing.